Pamamanhikan - Neri, Bernadette V. (Review of Women's Studies; Vol 23 No 1-2 (2013): Review of Women's Studies Volume XXIII, Numbers 1-2 (January-December 2013), 2023)
Pamamanhikan narrates the thoughts of a woman who is faced with a crisis of motherhood. Her youngest daughter, Ces, is coming home along with her partner, and she is confronted with the predicament of how to deal with her daughter's lover. The story takes place while she is preparing all the ingredients of her daughter's favorite dish. Not being an expert in concocting the most complex emotions, will she eventually find the exact recipe that complements her own feelings?